2019
DOI: 10.2215/cjn.04840419
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcomes of a Randomized, Double-Blind, Placebo-Controlled Study Assessing Safety and Efficacy of C1 Esterase Inhibitor for Prevention of Delayed Graft Function in Deceased Donor Kidney Transplant Recipients

Abstract: Background and objectivesDelayed graft function is related to ischemia-reperfusion injury and may be complement dependent. We previously reported from a randomized, placebo-controlled trial that treatment with C1 esterase inhibitor was associated with a shorter duration of delayed graft function and higher eGFR at 1 year. Here, we report longer-term outcomes from this trial.Design, setting, participants, & measurementsThis is a post hoc analysis of a phase 1/2, randomized, controlled trial enrolling 70 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…Moreover, its deleterious effect on graft life further subjects ILDKTr to adverse long‐term outcomes 6 . However, as DGF and AR generally precede mortality and graft loss, anticipating these events may lead to more effective management and response to therapy 8,15,18,19 . Therefore, characterizing the risk of these outcomes in ILDKTr is important and would better inform patient counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its deleterious effect on graft life further subjects ILDKTr to adverse long‐term outcomes 6 . However, as DGF and AR generally precede mortality and graft loss, anticipating these events may lead to more effective management and response to therapy 8,15,18,19 . Therefore, characterizing the risk of these outcomes in ILDKTr is important and would better inform patient counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary end point of DGF incidence was not met, significant reductions in need for dialysis and improvements in long-term allograft function were seen with C1-INH treatment. Recently, the long-term outcome of the trial has been updated and the researchers found that berinert treatment is associated with a lower incidence of graft failure [ 32 ]. These encouraging data suggest that complement inhibition is potentially valuable to prevent IRI damage in the clinic.…”
Section: Complement Activationmentioning
confidence: 99%
“…A phase 1/2 RCT (N = 70) reported a significant benefit of C1 esterase inhibitor (C1-INH) for 3.5-year allograft survival when given intraoperatively and 24 hours post-transplant. 130,131 In contrast, a large multi-centre registration RCT (PROTECT, N = 288) did not meet its primary endpoint to justify perioperative administration of eculizumab (a C5 inhibitor) to prevent delayed graft function, although long-term follow data were not collected (NCT02145182). In a cohort of pediatric kidney transplant recipients, a single pre-transplant dose of eculizumab led to significantly better graft function up to 3 years later, but was associated with an unacceptably high rate of early graft losses during a flu-like infection (all in non-vaccinated children).…”
Section: Novel Strategies To Target Alloantibody Effector Functionmentioning
confidence: 99%